Preparation and properties of oil palm empty fruit bunch grafted polyacrylic acid hydrogels for slow release fertilizer application - Rabat, Nurul Ekmi (2010)
Oil Palm Empty Fruit Bunch-grafted-Polyacrylic Acid (OPEFB-g-PAA) hydrogel was synthesized via solution copolymerization initiated by Ammonium Persulfate (APS) and N,N’-Methylenebisacrylamide (MBA) as crosslinker. Acrylic Acid has been partially neutralized with Sodium Hydroxide (NaOH) beforehand and the amount of AA was kept constant while OPEFB amount varied for every formulation: 0%,5%,10%, 20% and 30% of OPEFB-g-PAA. A mechanism for the reaction involved has been proposed based on Fourier Transform Infrared (FTIR) results. The swelling behaviour of OPEFB-g-AA tests consist of water and urea absorbency, gel content determination and reswelling ability. The results showed that the incorporation of 20% OPEFB in hydrogel gave the maximum amount of the water and urea absorbency at 83.4 g/g and 49 g/g respectively. The incorporation of 20% OPEFB in hydrogel had also increased the reswelling ability of hydrogels produced. Slow release of urea from hydrogel in water using Static Release Experiment and in soil using Column Method has been conducted. The absorptions of urea with indicator, p-dimethylaminobenzaldehyde from both methods were detected by Spectrophotometer. Hydrogel with 5% OPEFB had slower rate of release compared to the others while hydrogel with 0% OPEFB gave faster rate of urea released. This proved that OPEFB in the hydrogel helps to hold and slowing down the movement of urea from getting out from hydrogel. The addition of OPEFB in hydrogel also promotes the degradation in soil. Based on the soil burial test conducted for 42 days, 10% and 20% OPEFB-g-PAA have better biodegradability compared to others.